Designing rulemaking how regulatory policy instruments matter for governance - Dunlop, Claire 1974-; Kamkhaji, Jonathan; Radaelli, Claudio M. 1960-; Taffoni, Gaia; Wagemann, Claudius (Oxford University Press, 2024)
Over the years the Member States of the EU and the UK have redesigned rulemaking with freedom of information acts, impact assessment of policy proposals, ombudsman and stakeholder consultation. The broad aim of this instrumentation is both to improve on substantive regulatory quality and to impact on final governance outcomes. This book explains where and how the design of rulemaking procedures has effects on the quality of the business environment, perception of corruption, and environmental performance. The findings shatter predominant views on policy change in Europe, and offer a granular account of the efficacy of design.